Resource capture and use in semi-arid overstorey agroforestry systems - Lott, James E. (1998)
The work reported here aimed to provide a comprehensive database of core information to support the development and validation of process-based models of resource capture and growth in semi-arid overstorey agroforestry systems. Intensive field studies were carried out in Kenya over a 30 month period and the results obtained were combined with data from a previous project to produce a dataset spanning a 4.5 year period. This dataset was then used to verify output from the HyPAR model.